Analysis of Used Car Consumer Financing through Murabahah Contract in Islamic Banking - Yulianti, Mei Nurus Syamsiyah (Jurnal Ekonomi dan Bisnis, 2025)
This study examines the implementation of murabahah contracts in consumer financing for used motor vehicles by Islamic banks. With the rapid expansion of Islamic financial institutions in Indonesia, there is a growing demand for financing products that comply with sharia principles. Used car financing is increasingly favored as a more economical alternative to new vehicle purchases. This research explores how Islamic banks apply murabahah, a cost-plus sale mechanism, ensuring that ownership remains with the bank, prices are transparent, and elements such as riba, gharar, and maysir are avoided. Despite its benefits, financing used vehicles presents challenges such as asset depreciation, legal uncertainties regarding ownership, and undisclosed defects. This study investigates the risk management strategies adopted by Islamic banks, including evaluating customer eligibility, conducting asset appraisals, and strengthening legal documentation. Additionally, while consumer financing expands financial access, it is often considered less economically productive.